A Call for Low- and Middle-Income Countries to Commit to the Elimination of Cervical Cancer - Jacqueline Duncan; Michelle Harris; Nicola Skyers; Althea Bailey; John Peter Figueroa (Elsevier, 2021)
The World Health Organization has called for the global elimination of cervical cancer. While high income countries have made significant progress, the incidence and mortality due to cervical cancer is unacceptably high in low and middle income countries (LMIC). Jamaica is an upper middle income country with cervical cancer incidence and mortality of 21.6/100,000 and 13.6/100,000 person years respectively compared to 14.9/100,000 and 7.6/100,000 person years in Latin America and the Caribbean. Jamaica's pathway to reducing the burden of cervical cancer highlights challenges and opportunities for other LMIC. High prevalence of HPV infection (54% women attending primary care clinics), low levels of cervical cancer screening (<50% women 15 to 54 years old screened in the last 3 years) and suboptimal uptake of HPV vaccination (approximately 30%) are persistent barriers to achieving this goal. Lessons learned from the response to the human immunodeficiency virus (HIV) epidemic confirm the need for serious political commitment by global and national leaders, meaningful engagement of stakeholders and innovative strategies to improve uptake of HPV vaccination and cervical cancer screening. Commitment of technical and financial resources are critical for establishing robust cancer registries and strengthening monitoring and evaluation systems in LMIC.